A glance into the roles of microRNAs (exosomal and non-exosomal) in polycystic ovary syndrome - Afsane Masoudi Chelegahi; Seyed Omar Ebrahimi; Somayeh Reiisi; Maria Nezamnia (Obstetrics & Gynecology Science, 2024)
Polycystic ovarian syndrome (PCOS) is a common endocrine disorder in women of reproductive age. The clinical symptoms include hyperandrogenism, chronic anovulation, and multiple ovarian cysts. PCOS is strongly associated with obesity and insulin resistance. MicroRNAs (miRNAs) are a group of short non-coding RNAs that play a role in the post-transcriptional regulation of gene expression and translational inhibition. They play a vital role in the regulation of multiple metabolic and hormonal processes as well as in oocyte maturation and folliculogenesis in the female reproductive system. miRNAs can be used as diagnostic biomarkers or therapeutic targets because of their stability. The encapsulation of miRNAs in extracellular vesicles or exosomes contributes to their stability. Exosomes are constantly secreted by many cells and size of about 30 to 150 nm. Enveloping miRNAs exosomes can release them for cellular communication. The induced transfer of miRNAs by exosomes is a novel process of genetic exchange between cells. Many studies have shown that along with non-exosomal miRNAs, different types of exosomal miRNAs derived from the serum and follicular fluid can play an essential role in PCOS pathogenesis. These miRNAs are involved in follicular development and various functions in granulosa cells, apoptosis, cell proliferation, and follicular atresia. The present study aimed to comprehensively review the evidence on miRNAs and their affected pathways under both non-exosomal and exosomal circumstances, primarily focusing on the pathogenesis of PCOS.